2008
DOI: 10.1088/0957-4484/19/46/465706
|View full text |Cite
|
Sign up to set email alerts
|

The Pd catalyst effect on low temperature hydrogen desorption from hydrided ultrathin Mg nanoblades

Abstract: We present hydrogenation/de-hydrogenation properties of ultrathin Mg nanoblades coated with Pd as a catalyst. The hydrided Pd/Mg/Pd and Pd/Mg nanoblades were highly curved as observed by ex situ scanning electron microscopy. An in situ thermal desorption spectroscopy (TDS) study showed that the hydrided Pd/Mg/Pd nanostructure has a low hydrogen desorption temperature, at ∼365 K. Through a combinational microstructure and TDS analysis of hydrided Pd/Mg/Pd nanoblades as well as hydrided Pd/Mg/Pd nanoblades cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…In this respect, the sorption behavior of the current films, are quite similar to that found in Mg-based ultra thin films [22][23][24][25][26][27][28][29][30], i.e. thickness <100 nm, where they hydrogenate and dehydrogenate in nearambient conditions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this respect, the sorption behavior of the current films, are quite similar to that found in Mg-based ultra thin films [22][23][24][25][26][27][28][29][30], i.e. thickness <100 nm, where they hydrogenate and dehydrogenate in nearambient conditions.…”
Section: Discussionsupporting
confidence: 74%
“…Desorption temperatures are generally much lower for films of 15-100 nm thickness [22][23][24][25][26][27][28][29][30]. Qu et al [24] sputter deposited 100 nm Mg films on Si and glass substrates, and the resulting films were X-ray amorphous and could desorp hydrogen in air at temperatures of 298-328 K. Similarly, Richardson et al [26] produced Mg-Ni films of 80 nm thickness on a glass substrate and examined their optical switching properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that a Pd layer improves the kinetics of hydrogen absorption in many metals [5,6,7,8] including thin MgAl films. [9] The Pd layer prevents the formation of an oxide layer, and is likely to lower hydrogen dissociation and diffusion barriers prompting atomic hydrogen spillover into the bulk hydrogen absorbing phase.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of efforts have been devoted to overcome the barriers for the use of Mg alloys in hydrogen storage. It has been found that by reducing the particle size to nanoscale [2][3][4], adding catalysts [5][6][7][8] and fabricating thin films [9][10][11][12][13][14][15], the kinetic properties of Mg based hydride can be remarkably improved and the absorbing or desorbing temperature substantially reduced. For instances, MgH 2 with nanosize of around 5 nm can remarkably desorb hydrogen at 85 • C [3].…”
Section: Introductionmentioning
confidence: 99%
“…To explore the way of improving the performance of Mg based hydride and to reveal the related mechanism, Mg based thin films have been used as a model system [4,12,13,15]. In particular, Mg/Pd double-layer film has been investigated and Pd has been shown to be a good catalyst for the dissociation of hydrogen molecules and recombination of hydrogen atoms into molecules [12].…”
Section: Introductionmentioning
confidence: 99%